2011
DOI: 10.2147/nds.s13138
|View full text |Cite
|
Sign up to set email alerts
|

Personalized nutrigenomics: tailoring the diet to the aging diabesity population

Abstract: According to the International Diabetes Federation (IDF), 190 million people worldwide suffer from diabetes, and this number is estimated to double by the year 2025. Diabetes is especially prominent in the elderly population because the IDF indicates age above 45 years as a major risk factor for diabetes. The most common trials for controlling diabetes focus on tighter glucose control as a means to reduce the long-term complications. However, whether tight blood sugar control or other dietary or pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 123 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Eco-physiological and other studies have now established that secondary plant metabolites afford survival benefits to plants against enviorenmental stress (Kennedy, 2014a;Kennedy, 2014b;Trowbridge, 2014), and that structurally and functionally diverse edible phytochemicals possess pleiotropic protective effects against stress responses and are potentially useful for prevention and cure of diabetes, Alzheimer's disease and other chronic silently progressing chronic diseases (Dembinska-Kiec et al, 2008;Leiherer et al, 2013;Davinelli et al, 2012;Vaiserman, 2014;Carriba and Comella, 2014;Franco and Cedazo-Minguez, 2014;Ruden and Lu, 2011). However, it has been also reported that depending on the components of whole-food some of them could as well worsen cognitive dysfunctions (Parrott et al, 2015).…”
Section: Phytochemicals Stress and Diabesitymentioning
confidence: 99%
“…Eco-physiological and other studies have now established that secondary plant metabolites afford survival benefits to plants against enviorenmental stress (Kennedy, 2014a;Kennedy, 2014b;Trowbridge, 2014), and that structurally and functionally diverse edible phytochemicals possess pleiotropic protective effects against stress responses and are potentially useful for prevention and cure of diabetes, Alzheimer's disease and other chronic silently progressing chronic diseases (Dembinska-Kiec et al, 2008;Leiherer et al, 2013;Davinelli et al, 2012;Vaiserman, 2014;Carriba and Comella, 2014;Franco and Cedazo-Minguez, 2014;Ruden and Lu, 2011). However, it has been also reported that depending on the components of whole-food some of them could as well worsen cognitive dysfunctions (Parrott et al, 2015).…”
Section: Phytochemicals Stress and Diabesitymentioning
confidence: 99%